Recognizing and reducing corruption risks in land management in Vietnam (Ha Noi, 2011)
The book analyzes and explains the cause of corruption in land administration and the existing types of corruption
Keywords: Land use,Real estate managenent,Quản lý đất đai,Sử dụng đất; Corrupt practices,Tham nhũng; Vietnam,Vietnam,Việt Nam,Việt Nam